Hierarchy and diffusion of organizational forms - Fioretti, Guido; Neumann, Martin (Frontiers in Psychology, 2022)
In this paper we first of all summarize and rationalize current typologies of organizational forms, arranging available classifications in a hierarchy of increasing generality. The ensuing structure parallels the classification of living beings into classes of increasing generality such as species, genus, family, order, and so on. Subsequently, we analyze the structure of communications that favored the diffusion of each organizational form. We isolate a few stylized communication structures, pointing to the presence of several sources endowed with global connections as the most efficient diffusion mode. The empirical research that is being carried out on single organizations is close to observing their T-patterns, whereas nothing comparable is in sight for organizational forms as yet. However, at least in some cases, we dare to formulate tentative hypotheses on certain features that the ensuing T-patterns-of-patterns might exhibit.